Quality of life in pregnant women with sleep disorder. - Elham Rezaei; Zahra Behboodi Moghadam; Khadijeh Saraylu (Tehran University of Medical Sciences, 2013)
Objective: Sleep disorders are common complaints of women during pregnancy. These disorders are the result of physiological, hormonal, physical changes, affecting before, during, and right after pregnancy. This study aimed to evaluate the quality of life of pregnant women with sleep disorders in the second trimester. Materials and methods: In this cross-sectional study, data was collected with continuous sampling method. A total of 100 pregnant women with sleep disturbances in their second trimesters were recruited in this study. The participant referred to two elected health centers in West Azerbaijan University of Medical Science (One and three numbers of health care centers) in order to get prenatal care in the city of Maku, West Azerbaijan, Iran. The data was gathered using the personal information forms and the questionnaires, prepared by the World Health Organization Quality of Life (WHOQOL: BREF). To analyze the collected data, different statistical methods, like frequency tables, Pearson, Spearman and ANOVA were applied. Results:The results indicate that the mean sleep quality is 8.62 ± 2.81 in pregnant women with sleep disorders or poor quality of sleep in the second trimester. Quality of life (p ≤ 0.03) and one of domains, including psychological health (p ≤ 0.02) related to quality of sleep. Conclusion: Given that a large percentage of women suffer from sleep disorders in pregnancy, we hope during this period, in addition to usual care, codified programs is done to evaluate, detection and Diagnosis of this disorder.